2015
DOI: 10.3389/fneur.2014.00291
|View full text |Cite
|
Sign up to set email alerts
|

Transient Global Amnesia Associated with a Unilateral Infarction of the Fornix: Case Report and Review of the Literature

Abstract: Stroke is an extremely uncommon cause of transient global amnesia (TGA). Unilateral lesions of the fornix rarely cause amnesia and have not previously been reported to be associated with the distinctive amnesic picture of TGA. We describe the case of a 60-year-old woman who presented with acute onset, recent retrograde, and anterograde amnesia characteristic of TGA. Serial magnetic resonance imaging showed a persistent focal infarction of the body and left column of the fornix, without acute lesions in the hip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Some studies have found TGA patients to have higher vascular risk factors and greater frequency of carotid atherosclerosis, suggesting an atherosclerotic embolic event as a cause [4,20]. One final hypothesis is that TGA is a type of migrainous aura, occurring due to cortical spreading depression, leading to cellular metabolic stress in vulnerable CA-1 sector neurons [9,18,[21][22][23][24]. Genetics may also contribute to susceptibility, based on observations from limited case studies [15,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have found TGA patients to have higher vascular risk factors and greater frequency of carotid atherosclerosis, suggesting an atherosclerotic embolic event as a cause [4,20]. One final hypothesis is that TGA is a type of migrainous aura, occurring due to cortical spreading depression, leading to cellular metabolic stress in vulnerable CA-1 sector neurons [9,18,[21][22][23][24]. Genetics may also contribute to susceptibility, based on observations from limited case studies [15,[25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…The precommissural fibers connect to interstitial nucleus of stria teminalis, accumbens, anterior olfactory nucleus, nucleus of the diagonal band, and preoptic areas, while postcommissural fibers connect to thalamus, hypothalamus, and midbrain (Insausti and Amaral 2004). Lesions of the fornix have disruptive effects on the connectivity of the hippocampus, and result in deficits in memory formation (Gupta et al, 2014; Dumont et al, 2015). We showed that structures along the SHH pathway have morphometric and microstructural alteration in the CVN-AD model, notably reduced FA, and that the fornix FA could be predicted by the hippocampal volume (R 2 ~0.6).…”
Section: Discussionmentioning
confidence: 99%
“…Причиной грубых дефектов памяти, вплоть до транзиторной глобальной амнезии, может быть и острое изолированное повреждение свода (тела и его левой колонки) на фоне ишемического инсульта [24]. В противовес этому двустороннее повреждение свода опухолью, т.е.…”
Section: рис 2 мрт пациента н в режиме т1 (а) T2 Flair (б) и T2 (в)unclassified